Evaluation of Thyroid Hormones in Chronic Hepatitis C Patients on Oral Antiviral Therapy - Fawad Mahmood, Jahan Sardar, Sajjad Mohammad, Sajid Ali, Badi Uddin, Aamer Ali Khattak (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis C virus (HCV) is a major cause of morbidity and mortality. About 71 million people around the world are chronically infected with HCV, however, in Pakistan, approximately 12 million people are suffering from this dreadful virus. In Pakistan, approximately 6.2 % of population is infected with HCV and its treatment rate is approximately 1 %. The aim of this research was to assess thyroid hormones level in chronic HCV patients which were taking the oral-antiviral therapy. Methods: A total of 1650 suspects were screened by immunochromatographic technique. Then ELISA technique were used to confirmed the sample and PCR were also performed. All data were analyzed through Microsoft Excel and SPSS-21. Results: Out of total ICT positive, 117 patients were positive for HCV. Subsequently, all positive samples were exposed to Enzyme linked Immunosorbant assay, out of 117 tested samples 112 (6.7 %) were found positive. However, the final confirmation was done by using Real Time PCR, which showed 109 (6.6 %) patients positive for HCV. Among these 109 HCV patients, the age-wise prevalence of HCV patients was observed maximum 35 (32 %) in age group (55-74 years). Furthermore, these 109 patients were tested for the thyroid dysfunction, before and after anti-viral therapy (Sofosbuvir and Daclatasvir therapy) which was recommended by World Health Organization. Out of 109 HCV positive patients the frequency, 92 (84.6 %) showed euthyroidism, 6 (5.5 %) hypothyroidism and 11 (10 %) hyperthyroidism. Thyroid dysfunction was high (n=17, 15.6 %) in patients with age above 50 years. Six (35.2 %) of thyroid dysfunction patients revealed hypothyroidism and hyperthyroidism was observed in 11 (64.7 %) patients. Mean values of thyroid function test before antiviral therapy were TSH = 3.88 ± 1.0, TT3 = 1.15 ± 0.58, and TT4 = 7.7 ± 01.99 and mean values after three months therapy were TSH = 2.49±1.72, TT3 =1.38 ± 0.69 and TT4 = 8.78 ± 2.29. Conclusion: It is concluded that HCV infected individuals on oral antiviral drugs have an effect on the thyroid gland, therefore, HCV patients should be frequently screened for thyroid disorders before and after treatment to ensure euthyroid status. Keywords: Thyroid hormones, Hepatitis, Oral Anti-viral therapy, Thyroidism